Determination of Diffusion Coefficients of L-(+) - Tartaric Acid in Water and Sodium Hydroxide Solutions at 25˚c - Kipkosgei , Moses; Muthoka, Titus Muthama; Anditi , Collins (African Journal of Education,Science and Technology (AJEST), 2013)
Food additives play a vital role in today‟s bountiful and nutritious food supply and their migration in water is a diffusion process governed by Fickian diffusion laws. The study looked into the rate of diffusion of L-(+) - tartaric acid at 25˚C in water and in NaOH solution of different concentrations. L-(+) - tartaric acid and its salts are approved as food additives, with acidulant, antioxidant synergist, buffering and sequestraring functions. The objective of the work was to determine the diffusion coefficient using spectrophotometric method and moving boundary method and to compare the diffusion coefficients obtained with those calculated from limiting ionic conductance at infinite dilution. The absorbance at different height levels ( )were measured at a given time and at specific wavelength. The boundary heights () at a time t and concentration were also recorded. The diffusion coefficients were obtained from slopes of the ln A vs 2 and 2 vs t graphs which are governed by the Fick‟s second law and square-root relationship respectively. The spectrophotometric diffusion coefficient ranged from - 2.5445 x 10-05 to -7.96674 x 10-06 cm2/sec and for moving boundary method were between 1.2974 x 10-04 and 7.4908 x 10-05 cm2/sec for L-(+) - tartaric acid. Spectrophotometric diffusion coefficients values were in a close agreement with the expected Do value unlike moving boundary which gives reasonable but rough estimation of diffusion coefficients in the range of x 10-05 cm2/sec. Spectrophotometric method is also preferred because of its practicability and applicability under ordinary laboratory conditions which is in agreement with the principles for the establishment of the codex method of analysis.